2015
DOI: 10.1111/etp.12074
|View full text |Cite
|
Sign up to set email alerts
|

Root filling materials and techniques: bioceramics a new hope?

Abstract: Instrumentation creates space for canal irrigation, disinfection and root filling. All of these have an impact on the method and size of instrumentation, depending on the philosophy of the dentist and the limitations and requirements set by the equipment used in each phase, especially in root filling. Optimal root filling has many requirements which have been difficult if not impossible to fulfill. Gutta‐percha has been and still is the core material of choice in root fillings, but it requires the use of a sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 59 publications
1
80
0
13
Order By: Relevance
“…, Trope et al . , Wang ). In laboratory studies, it has been reported to have excellent biocompatibility and sealing ability, as well as being associated with desirable clinical outcomes when used for repair of perforations, vital pulp therapies, root‐end fillings and root fillings, and when used as an apical plug (Parirokh & Torabinejad , Torabinejad & Parirokh ).…”
Section: Introductionmentioning
confidence: 99%
“…, Trope et al . , Wang ). In laboratory studies, it has been reported to have excellent biocompatibility and sealing ability, as well as being associated with desirable clinical outcomes when used for repair of perforations, vital pulp therapies, root‐end fillings and root fillings, and when used as an apical plug (Parirokh & Torabinejad , Torabinejad & Parirokh ).…”
Section: Introductionmentioning
confidence: 99%
“…MTA and BC fast set putty belong to a calcium silicate-based group of materials. During the hydration reaction, endodontic bioceramics release Ca(OH) 2 , which interacts with phosphates in the tissue fluids to form hydroxyapatite and tag-like structures in dentin [40]. BC fast set putty is premixed by the manufacturer and has a more homogenous and smaller particle size than MTA.…”
Section: Discussionmentioning
confidence: 99%
“…When bioactive bioceramic materials come into contact with tissue fluids, they are believed to release calcium hydroxide and interact with phosphates, forming hydroxyapatite. Some of these materials, such as calcium silicate‐based cements (MTA), are considered the material of choice for endodontic treatment errors such as perforation repair, and also for root‐end filling or obturation of teeth with open apices . The possibility to “remineralize” the interface with bioceramic sealers is a tempting goal because both the strength and tightness of the interface could increase with time.…”
Section: Dentin/host Factors Which Alter the Integrity Of The Dentin–mentioning
confidence: 99%
“…Although the role of MMPs in the degradation of dentin matrix in caries lesions had been sustained previously , the first direct evidence of this occurrence in non‐carious dentin matrix came when Pashley and co‐workers showed that acid‐etched dentin was gradually degraded in the absence of bacteria . Afterwards, a number of articles employing various techniques have confirmed that proteinases are present in human mineralized dentin and may become active after demineralization via a variety of methods .…”
Section: Dentin/host Factors Which Alter the Integrity Of The Dentin–mentioning
confidence: 99%